Parameters of the type-IIP supernova SN 2012aw. Issue 3 (19th April 2021) - Nikiforova, A A; Baklanov, P V; Blinnikov, S I; Blinov, D A; Grishina, T S; Troitskaya, Yu V; Morozova, D A; Kopatskaya, E N; Larionova, E G; Troitsky, I S
ABSTRACT: We present the results the photometric observations of the Type IIP supernova SN 2012aw obtained for the time interval from 7 to 371 d after the explosion. Using the previously published values of the photospheric velocities, we have computed the hydrodynamic model which simultaneously reproduced the photometry observations and velocity measurements. We found the parameters of the pre-supernova: radius R = 500 R ⊙, nickel mass M ( 56 Ni) 0.06 M_, pre-supernova mass 25 M⊙, mass of ejected envelope 23.6 M⊙, explosion energy E ∼ 2 × 10 51 erg. The model progenitor mass M = 25 M⊙ significantly exceeds the upper limit mass M = 17 M⊙, obtained from analysis the pre-SNe observations. This result confirms once more that the 'Red Supergiant Problem' must be resolved by stellar evolution and supernova explosion theories in interaction with observations.